Hydrodynamics of a hyper-tidal estuary influenced by the world's second largest tidal power station (Rance estuary, France). (5th March 2021) - Rtimi, Rajae; Sottolichio, Aldo; Tassi, Pablo
Abstract: The Rance estuary is a relatively small low-discharge steep-sided ria, located along the Brittany coast in northern France, with a maximum spring tidal range of 13.5 m. Taking advantage of this hyper-tidal regime, the first and currently the second largest operational tidal power station in the world was built at the estuary's mouth and has been in operation since the 1960s. Despite the well-known effect of damping of estuarine water levels, little attention has been given to quantifying the influence of the plant on the propagation and asymmetry of the tidal wave inside the estuary. In this study, hydrodynamics and tidal wave patterns were analyzed in this anthropogenically influenced estuarine system. A two-dimensional depth-averaged numerical model of the Rance estuary was developed. Two scenarios without the tidal power plant involving the dam's pre- and post-construction bathymetry (1957 and 2018 respectively) and present-day conditions scenarios were designed, to highlight the impact of bed evolution and the tidal power station on hydrodynamics and tidal asymmetry. Numerical results showed that, without the structure, bathymetric evolution did not substantially influence estuarine hydrodynamics. Nevertheless, on the estuary-side of the dam, the presence of the tidal power plant induced (i) a decrease in both tidal range and tidal prism, (ii) an increase of low water levels, and (iii) a decrease in both flood and ebb currents. Contrastingly, the region close to the structure reacted differently to plant operating modes, with an increase in flood currents (ebb currents) upstream of the sluice gates (downstream of the turbines). For both the natural condition and the artificially-induced hydrodynamic forcing due to the presence of the plant, numerical results showed that the Rance estuary mainly exhibits flood-dominant behavior, with a longer duration of falling than rising water and stronger peak flood currents than ebb currents. Spanning a period of approximately 60 years, this study presents a quantitative analysis of the influence of the tidal power station on the hydrodynamics in the Rance estuary, and its possible consequences for sediment dynamics. This approach is novel for this particular enclosed water body, characterized by the presence of a dam at its mouth and a lock at its uppermost limit. Highlights: Quantitative analysis of hydrodynamics and tidal patterns of Rance estuary, influenced by a tidal power station. In the absence of the plant, changes in bathymetry does not have significant influence on the estuarine hydrodynamics. The plant decreases tidal range, currents and tidal prism inside the estuary. The tidal power station increases the estuarine low-water level and elongates period of slack water and residence time. Tidal patterns analysis suggest that the tidal power plant does not impact the origin of sediments present inside the basin.